2021
DOI: 10.1007/s11032-021-01271-8
|View full text |Cite
|
Sign up to set email alerts
|

A QTL on the Ca7 chromosome of chickpea affects resistance to the root-lesion nematode Pratylenchus thornei

Abstract: HatTrick, and a very susceptible cultivar, Kyabra. A genetic linkage map was constructed from genotyping-by-sequencing data. Two quantitative trait loci were mapped, one on the Ca4 chromosome and one on the Ca7 chromosome. The Ca7 locus had a greater and more consistent effect than the Ca4 locus. Marker assays designed for single nucleotide polymorphisms on Ca7 were applied to a panel of chickpea accessions. Some of these markers should be useful for markerassisted selection in chickpea breeding. Haplotype ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Applications of SB include the development of biparental and more complex mapping populations, pyramiding traits, hastening backcrosses, phenotyping adult plant traits, mutant studies, and genetic transformation experiments [ 7 , 29 ]. Recent research has shown the power of combining emerging techniques, such as gene editing, high-throughput phenotyping and genotyping, genomic selection (GS), and MAS, with SB for accelerating crop improvement [ 30 , 40 , 42 , 43 , 44 , 45 , 46 ]. Furthermore, the cost and space requirements for producing a large number of inbred lines can be minimized by planting them at high plant densities [ 47 ].…”
Section: Sb Applications In Research and Breedingmentioning
confidence: 99%
See 2 more Smart Citations
“…Applications of SB include the development of biparental and more complex mapping populations, pyramiding traits, hastening backcrosses, phenotyping adult plant traits, mutant studies, and genetic transformation experiments [ 7 , 29 ]. Recent research has shown the power of combining emerging techniques, such as gene editing, high-throughput phenotyping and genotyping, genomic selection (GS), and MAS, with SB for accelerating crop improvement [ 30 , 40 , 42 , 43 , 44 , 45 , 46 ]. Furthermore, the cost and space requirements for producing a large number of inbred lines can be minimized by planting them at high plant densities [ 47 ].…”
Section: Sb Applications In Research and Breedingmentioning
confidence: 99%
“…Since 2016, SB has been integrated within all cool-season legume public breeding programs in Australia, with more than 45,000 individuals processed through an aSSD platform at the University of Western Australia. The resulting RILs have been used for gene-trait associations [ 43 , 44 , 45 , 46 ], and SB has been integrated with other technologies to accelerate cultivar development pipelines [ 40 ].…”
Section: Model Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 18 Australian chickpea varieties and 29 breeding lines were obtained from Dr Kristy Hobson of the Chickpea Breeding Australia (CBA) programme at the New South Wales Department of Primary Industries (NSW-DPI, Tamworth, NSW, Australia). In addition, an F 7 recombinant inbred line (RIL) population (n = 200) derived from cultivars PBA HatTrick and Kyabra (Khoo et al 2021) was used.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Cultivated chickpea has a high morphological diversity but narrow genetic variation for trait improvement (Udupa et al 1993;Abbo et al 2003); therefore, research on whether SSR resistance alleles exist in this narrow gene pool is needed. Recently, a RIL population derived from Australian cultivars PBA HatTrick and Kyabra was employed to map QTLs associated with resistance to the root-lesion nematode Pratylenchus thornei (Khoo et al 2021). The parents of this population differ in their responses to S. sclerotiorum infection, with PBA HatTrick having partial stem resistance (Mwape et al 2021a(Mwape et al , 2021b.…”
Section: Introductionmentioning
confidence: 99%